Optimized Dual Loop Control in PV – based LVDC Microgrid With Hybrid Energy Storage for Enhanced Power Management - D., Roshini; S., Sowkarthika (Journal of Electrical Engineering and Automation, 2025)
This study proposes a power management plan for an LVDC (Low-Voltage Direct Current) microgrid that is linked with solar energy and connected to a HESS (Hybrid Energy Storage System) that consists of a supercapacitor and battery. This study analyses the microgrid’s performance with a focus on integrating hybrid energy storage devices to manage the unpredictable nature of renewable energy resources and load demands. The primary goals are creating a DC link voltage controller, building the battery and supercapacitor current controller, and activating a solar power generating unit using the Perturb and Observe MPPT algorithm. Additionally, a dual loop control strategy is created for the HESS. The power management method controls DC voltage and maintains power balance.